Heterogeneous water phase catalysis as an environmental application: a review - Pirkanniemi, Kari; Sillanpää, Mika (Chemosphere (Oxford), 2002)
Catalytic water phase processes as an environmental application is a relatively novel subject with tremendous potential in the near future. This review of 120 references presents the wide scale of heterogeneous water phase applications studied mainly within past five years. Both oxidation and hydrogenation processes are included as well as TiO 2 assisted photocatalysis. According to the references, heterogeneous catalysis is developing rapidly. New bimetallic catalysts and supports with higher surface area have improved catalytic efficiency in both oxidation and hydrogenation processes. It also seems that study on use of some waste materials such as red mud as catalyst is a very progressive field. On the whole, the chemical aspects are pretty well known, but the catalyst durability, and in many cases activity as well, has to be improved.